Pembuatan produk ramah lingkungan: pemanfaatan limbah kain perca dan masker sekali pakai menjadi kotak pensil dan sandal hotel - Fahmi, Ismail (Maliki Interdisciplinary Journal, 2023)
Recently, the accumulation of patchwork waste and disposable mask waste has triggered a new problem. There are various kinds of dangers that threaten living things if this accumulation continues, such as water pollution in the oceans that causes marine animals to die and the spread of new viruses if the waste is left untreated. The purpose of this study was to determine the use of disposable mask waste and also patchwork to be used as materials for making pencil boxes and hotel slippers. The method used in this research is the experimental method, namely by conducting experiments that have been arranged by researchers to get good results. In this case, the resulting experiment is a pencil case and hotel slippers. The results obtained are pencil boxes and hotel slippers that are suitable to be used as environmentally friendly products, and can reduce waste in the environment and are able to stop the virus chain.